(untitled) (Scientific journal of the Fergana State University, 2023)
The first sign that makes a person a person and distinguishes him from the animal world is that he has the ability to speak. It is because of this miracle that a person conveys his feelings and thoughts to others. There is no more convenient tool for forming and developing the feeling of patriotism, which is one of the unique human qualities, than public speaking. In the article the theme of eloquence and patriotism is analyzed in the linguistic-cultural-pedagogical aspect.